2015
DOI: 10.1021/acs.jpca.5b05773
|View full text |Cite
|
Sign up to set email alerts
|

Rotation/Torsion Coupling in H5+, D5+, H4D+, and HD4+ Using Diffusion Monte Carlo

Abstract: Two methods for studying the rotation/torsion coupling in H5(+) are described. The first involves a fixed-node treatment in which the nodal surfaces are obtained from a reduced dimensional calculation in which only the rotations of the outer H2 groups are considered. In the second, the torsion and rotation dependence of the wave function is described in state space, and the other internal coordinates are described in configuration space. Such treatments are necessary for molecules, like H5(+), where there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The fact that the spectrum does not change when the value of the torsion angle is shifted from 90 to 0° suggests that, while the torsion is indeed large amplitude, its motion is nearly completely decoupled from the other vibrations considered in this study. This is consistent with the results of earlier work using DMC …”
Section: Resultssupporting
confidence: 94%
“…The fact that the spectrum does not change when the value of the torsion angle is shifted from 90 to 0° suggests that, while the torsion is indeed large amplitude, its motion is nearly completely decoupled from the other vibrations considered in this study. This is consistent with the results of earlier work using DMC …”
Section: Resultssupporting
confidence: 94%
“…The computations showed that H + 5 has a peculiar rotational-vibrational energy level structure, classifying this molecule as a prototypical astructural molecule. Marlett et al 35 confirmed this assessment and extended the DMC computations to rovibrational states of D + 5 , H 4 D + , and HD + 4 . As to experiments, in 2010 Cheng et al 37 reported experimental infrared spectra in the 2000-4500 cm −1 region.…”
Section: Reference Structure Bmentioning
confidence: 76%
“…The rotational energy levels utilized differ substantially from those of later, more elaborate studies. 8,35 Previous efforts 7,8 in our laboratory were carried out to compute and understand the rotational-vibrational energy level structure of H + 5 . The computations showed that H + 5 has a peculiar rotational-vibrational energy level structure, classifying this molecule as a prototypical astructural molecule.…”
Section: Reference Structure Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, on the vibrationally averaged PES the ∼60 cm −1 electronic barrier, hindering the proton hopping motion between the two sides, disappears, resulting in no difference in the “left” and “right” H 2 units for H5+ [H 2 –H–H 2 ] + . Unlike in the case of semirigid molecules, the lack of a clear structure makes the rovibrational energy‐level set of H5+ challenging to anticipate as well as to interpret …”
Section: Examples Of Quasistructural Moleculesmentioning
confidence: 99%